The Keseimbangan Pasar: Telaah Etika Bisnis Al-Maqrīzī terhadap Flash Sale di TikTok Shop - Ahmad Romdhoni; Yoiz Shofwa Shafrani; Muhammad Fathurrizqi Arief (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The phenomenon of flash sales on TikTok Shop has significantly revolutionized consumption patterns in Indonesia by offering massive discounts within strictly limited timeframes. While economically efficient for driving sales volume, this aggressive marketing strategy often encourages impulsive behavior among consumers, which, from an Islamic perspective, can be categorized as isrāf (wastefulness) and exposes transactions to gharar (uncertainty/ambiguity). This study aims to deeply analyze the influence of discount euphoria on consumption behavior and its ethical implications through the classical economic lens of Al-Maqrīzī. Using a qualitative descriptive method with a library research approach, this study critically analyzes Al-Maqrīzī's masterpiece, Ighāthat al-Ummah bi-Kashf al-Ghummah, and juxtaposes it with contemporary digital market phenomena (2019-2025). The results indicate that the euphoria of flash sales creates an illusion of need, driving consumption behavior that contradicts the Islamic principles of I’tidāl (moderation) and ‘adl (justice). In Al-Maqrīzī’s view, such practices reflect a loss of moral control in the market, similar to the economic distortions of the Mamluk era. Consequently, this study suggests that Al-Maqrīzī’s thought provides a vital foundation for building an ethical digital economy through the implementation of a digital hisbah mechanism, enhanced Islamic consumption literacy, and strict regulations to ensure transparency and justice in online transactions.